Legal pluralism. analysis of historical times (2019)
Through the analysis of historical times we can verify that legal pluralism has dominated most of our history. Although modern law initially sought to centralize political and legal power in the Nation-State, based on supremacy of the law and the formal equality of citizens; the search for justice and material equality brings back legal pluralism within the State. It is important to study legal pluralism in our societies because nowadays it is common to verify that different normative bodies do not coordinated and overlap. Also, being aware of the existence of several valid normative bodies helps us to be more open to other perspectives. © 2019 Universidad Externado de Colombia. All rights reserved.